Investigation of genetic association between PRODH gene and schizophrenia in Iranian population - Rahman zadeh, Saeid; Shahbaz Mohammadi, Hamid; karimipour, Morteza; Heidari keshel, Saeed (Archives of Advances in Biosciences, 2012)
Schizophrenia is a complicated, debilitative mental disorder. Evidence is emerging for the association of polymorphisms in PRODH gene and increased risk of schizophrenia. In the present research, we investigated relationship between of this gene and schizophrenia disease by means of a gene polymorphism using PCR-RFLP technique.150 persons suffering from acute Schizophrenia and 160 healthy persons volunteering for this project were bled. . Based on intended SNP, pair of primers was designed by Oligo7 program and polymerase chain reaction (PCR) was performed by thermo cycler. Then the resulted reactive mixture was exposed to a special enzyme, which we had intended for our study. Finally, the fragments of enzyme cut were transferred on the gel (4%) and migration pattern of resulted components were compared in healthy and patient subjects , whereby obtaining genotypes of different persons in polymorphic position. We utilized SPSS 16.0 program for statistical investigation of the work and studied SNP 1945T>C and its relation with the disease in statistical population. Our findings showed a meaningful relation between the occurrence of this nucleotide mutation and its frequency in patients (given P value=0.00). Results of this work indicate that PRODH gene can be considered to be a significant candidate in our population as a factor influencing the occurrence of Schizophrenia.